2021
DOI: 10.1186/s12885-021-08126-7
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-score-matching analysis to compare efficacy and safety between 16-gauge and 18-gauge needle in ultrasound-guided biopsy for peripheral pulmonary lesions

Abstract: Background Definitive diagnosis of peripheral pulmonary lesions (PPLs) depends on the histological analysis of the pleural biopsy sample. Ultrasound (US)-guided sampling is now standard practice in the clinical setting. However, determining a suitable needle size and sampling times to improve the efficacy and safety of the biopsy remains challenging. Here, we compared the efficacy between 16- and 18-gauge core biopsy needles in US-guided percutaneous transthoracic biopsy for PPLs on histologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Previous experience demonstrated that a 16-G needle provided a higher success rate during biopsy for PPLs compared with an 18-G needle. 14 As effective lesion sampling is paramount, identifying the factors that influence sample adequacy and safety is an important consideration for radiologists who perform thoracic interventions with 16-G needles. The present results showed that lesion size was an independent factor that influence sample adequacy, while patient position was an independent factor that influence overall complication and post-procedural haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experience demonstrated that a 16-G needle provided a higher success rate during biopsy for PPLs compared with an 18-G needle. 14 As effective lesion sampling is paramount, identifying the factors that influence sample adequacy and safety is an important consideration for radiologists who perform thoracic interventions with 16-G needles. The present results showed that lesion size was an independent factor that influence sample adequacy, while patient position was an independent factor that influence overall complication and post-procedural haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…A 16-G needle could achieve a larger volume of tissue compared with a smaller size needle that is utilised routinely in clinical application at present. 14 It seems that a 16-G needle is capable of achieving sample adequacy for successful diagnosis regardless of number of needle passes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors affecting diagnostic yield include needle size and needle type. Huang et al (24) have noted better success rates with a 16-gauge needle compared to 18-gauge needles for USG-guided peripheral lung biopsies. On the other hand, Cheung et al (25) noted no difference in sample adequacy with different needle sizes in the case of CT-guided lung biopsies.…”
Section: Discussionmentioning
confidence: 99%